Stakeholder Insights and Presidential Capital: Leadership Turnover and Its Impact on Higher Education - Trina Fletcher; Ahlam Alharbi; Lesia Crumpton-Young (Education Sciences, 2025)
Historically Black colleges and universities (HBCUs) in the United States have been experiencing a leadership turnover crisis, with 23 president and chancellor changes announced in 2022 and 41 in 2023. A survey of HBCU stakeholders at the 2023 White House Initiative on HBCUs was conducted to identify high-impact areas linked to this turnover, focusing on areas critical to the advancement and sustainment of HBCUs through the eyes of HBCU stakeholders. Additionally, it attempted to understand how campus dynamics and challenges can impact leaders using capital theory. The survey identified internal and external challenges, including engagement, morale, support, and retention across various stakeholders, suggesting that the turnover crisis needs to be viewed from the perspective of leaders’ turnover rather than leadership turnover. It was concluded that leaders’ forms of capital are compromised by misaligned campus dynamics, negatively impacting morale and engagement, leading to distrust, lack of support, pushback, and attrition. Therefore, leaders’ capitals can be depleted, leading to frustration, burnout, and ultimately voluntary resignation. The findings are crucial for institutions and leaders to understand and, most importantly, mitigate the impact of leader turnover on institutions, which demand stability.